Driving Factors of Deforestation In Indonesia: A Case of Central Kalimantan - Ely Susanto; Nanik Lestari; Maharani Hapsari; Krisdyatmiko Krisdyatmiko (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2018)
As one of countries which has the large tropical forests in the world and the largest in ASEAN, Indonesia has been facing serious deforestation problems. Eventhough some scholars have found causes of the deforestation and have tried to give solutions, however, identifications of deforestation causes are still worth studying as the deforestation still becomes an important issue in Indonesia. This study tries to extend and explore the causes of deforestation in Central Kalimantan, one of Provinces in Indonesia which has been facing the deforestation problem caused by many factors. This study applied a qualitative approach. Data were collected by using interview and focus group discussions which involved about 27 informants representing 14 organizations leaders such as WALHI, AMAN, Save Our Borneo, Yayasan Bentang Borneo, Ampuh, TUK Jakarta, Greenpeace, SIEJ, SPKS, Sawit Watch, Forest Watch Indonesia, Mongabay, Institute Dayakologi, LINK-AR Borneo, WWF and Academia as informants. The study found several factors that drive deforestation which are asymmetric deforestation concept, governance issues and commodity-based development politics.